Flexural behavior of hybrid FRP-recycled aggregate concrete-steel hollow beams. (January 2023) - Zhang, Liwen; Zhang, Junjie; Chen, Guangming; Lin, Guan
Abstract: Hybrid fiber reinforced polymer (FRP)-concrete-steel (FCS) hollow members are a new form of structural members possessing superior mechanical behavior and durability. Such members consist of an outer FRP tube, one or more inner steel tubes, and the concrete filled between the tubes. Existing studies on such members have been mainly focused on their use as columns; limited studies have been conducted on their use as flexural members. Besides, the effect of shear connectors between the steel tube and the concrete on the behavior of hybrid FCS hollow flexural members has not been investigated in detail. This paper, therefore, presents the results of an experimental program on the flexural behavior of hybrid FCS hollow beams with a rectangular hollow cross section. Recycled aggregate concrete (RAC) was used for the purposes of addressing the serious issue of construction waste nowadays and capitalizing the advantage of FRP confinement in enhancing the performance of RAC. The test results showed that such hybrid FCS hollow beams are very ductile, and the shear connectors play a significant role on the behavior of such beams. Finally, a theoretical beam model based on conventional section analysis was proposed to predict the results of the test hybrid FCS hollow beams. Highlights: Twenty-two rectangular hybrid FRP-concrete-steel (FCS) hollow beams with RAC were tested. Recycled aggregate concrete (RAC) was used for the purposes of addressing the serious issue of construction waste. The test hybrid FCS hollow beams exhibited very ductile behavior. Shear connectors played a significant role on the behavior of hybrid FCS hollow beams.